The passage of Maori land into Pakeha ownership: a Maori view - Williams, Betty Whaitiri (Cabbage Tree, 1983)
Keywords: colonisation; history; kōrero nehe; land alienation; land loss; land march; land tenure; land theft; mana whenua; missionaries

Transformations in Māori Women's Identity: Some Things Change, Some Stay the Same - Houkamau, Carla Anne (Qualitative Research in Psychology, 2011)
While Māori (the indigenous people of New Zealand) retain a strong collective identity, cultural heterogeneity renders traditional conceptualisations of Māori identity increasingly problematic. To demonstrate the diverse ways Māori define and express their own identities, this article reports research that uses life-story interviews to explore personal perceptions of identity among 35 Māori women ages 18–75. Content analysis revealed traditional cultural factors (particularly whānau/family commitment) were important for identity among all participants, although the expression of these factors differed along with age and background. Older women raised in rural communities expressed family commitment through participating in social and economic activities within their own tribal networks. Younger, urbanised Māori expressed their identities by choosing careers which advanced Māori interests, supporting Māori political aspirations, and forming close relationships with other urban Māori. Life-story excerpts are used to illustrate distinct intergenerational differences in expressions of Māori identity as well as descriptions of “Māoriness,” seldom articulated in literature on the topic. The need to expand current paradigms of Māori identity to incorporate the diversity of group members is emphasised.
Keywords: colonisation; ethnic identity; kaumātua; mana wāhine; māori identity; urbanisation

Globalisation and the Colonising State of Mind - Jackson, Moana (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: colonisation; globalisation; neoliberalism; protest

The Critical Juncture in Aotearoa New Zealand and The Collective Future: Policy Issues in Settler/Invader Colonial Zombiism Found in “Biculturalism” - Simon, Hemopereki (International Journal of Critical Indigenous Studies, 2022)
This research examines the settler colonial legacy of Aotearoa New Zealand. It shows that biculturalism has emerged as a discursive byproduct of neoliberalism and settler colonialism. Simon’s recent work and the Te Paparahi o Te Raki Waitangi Tribunal decision aligns with the view of a significant paradigm shift since biculturalism suppresses affirmation of and mana motuhake. Biculturalism can be viewed through Moreton-Robinson’s white possessive lens as well as Beck's zombie concepts, which are used to prop up deteriorating and/or fictional social institutions. As a zombie concept in Aotearoa New Zealand, “biculturalism” supports settler/invader power structures. Indigenous communities disproportionately experience the destructive consequences of neoliberal policies and statecraft. Aotearoa New Zealand’s collective future requires abandoning biculturalism; to that end the author recommends revising common historiographic thought concerning Te Tiriti o Waitangi (Treaty of Waitangi) and the concept of “settling”.
Keywords: bicultural; colonisation; neoliberalism

The meaning of biculturalism - Walker, Ranginui (R.J. Walker, 1986)
Keywords: bicultural; capitalism; colonisation; race relations; tiriti o waitangi/treaty of waitangi

Making our place: exploring land-use tensions in Aotearoa New Zealand - Ruru, Jacinta; Abbott, Mick; Stephenson, Janet (Otago University Press, 2011)
Keywords: colonisation; economic aspects; environment; land tenure; land use; social aspects; treaty negotiations

The balance destroyed: the consequences for Māori women of the colonisation of Tikanga Māori - Mikaere, Annabel (Published Jointly by the International Research Institute for Māori and Indigenous Education and Ani Mikaere, 2003)
Keywords: colonisation; crown law; european influences; mana wāhine; sexism; social conditions; social life and customs; wāhine māori

Back to the future: Maori Survival in the 1990s - Williams, Joe (Puna wairere: essays, 1990)
Keywords: colonisation; ethnic identity; social conditions; tiriti o waitangi/treaty of waitangi

Chapter Two: Rangatiratanga, Kawanatanga and the Constitution - Walker, Ranginui (A land of milk and honey?: making sense of Aotearoa New Zealand, 2017)
"Since colonisation, New Zealand has been mythologised as a 'land of milk and honey' - a promised land of natural abundance and endless opportunity. In the twenty-first century, the country has become literally a land of milk and honey as agricultural exports from such commodities dominate the national economy. But does New Zealand live up to its promise? In this introductory textbook for first year sociology students, some of this country's leading social scientists help us to make sense of contemporary New Zealand. In 21 chapters, the authors examine New Zealand's political identity and constitution; our Māori, Pākehā, Pacific and Asian peoples; problems of class, poverty and inequality; gender and sexualities; and contemporary debates around ageing, incarceration and the environment. The authors find a complex society where thirty years of neoliberal economics and globalising politics have exacerbated inequalities that are differentially experienced by class, ethnicity, gender, sexuality and age. These social divides and problems are at the heart of this text. For sociology students and for a wider audience of New Zealanders, A Land of Milk and Honey? is a lively introduction to where we have come from, where we are now, and where New Zealand society might be headed"--Back cover.
Keywords: colonisation; he whakaputanga; kāwanatanga; kīngitanga; rangatiratanga; social change; social conditions; social life and customs; tiriti o waitangi/treaty of waitangi; treaty settlements

Colonization, whenua and capitalism: experiences from Aotearoa New Zealand - Moewaka Barnes, Helen; Eich, E.; Yessilth, S. (Continuum, 2018)
The English Laws Act, passed in 1858, declared the Laws of England applicable in New Zealand and cemented the hitherto alien ideology of land as property. Part of this ideology was the separation of tangata from whenua along with the separation of ownership of land from ownership of water. Māori, as tangata whenua – people of the land, made no such distinctions. Ownership affects how people ‘manage’ whenua (land), make decisions and account to the legal system. Under English law, financial considerations are at the forefront. In contrast, Māori kaitiakitanga values are concerned with the interests of land, understanding that the best interests of people will follow. Despite stark contrasts between the ideology of land as property and the ethics of kaitiakitanga – obligation, sustainability and nurture – Māori engage with mainstream agencies and lead by example in efforts to promote the wellbeing of people and environments in a unified approach. This paper outlines competing paradigms, changing relationships and challenges faced by communities who seek to nurture and respect whenua in the face of colonization. Interview data from Māori involved in community land-based initiatives illustrates past and present struggles and what some possibilities might be for the future.
Keywords: capitalism; colonisation; crown law; kaitiakitanga; whenua

Tension without tikanga: the damaging face of the treaty claims settlement system - Taiapa, Ken; Moewaka Barnes, Helen; McCreanor, Tim (AlterNative: An International Journal of Indigenous Peoples, 2021)
In Aotearoa New Zealand, the arrival of imperial ideologies in the 19th century led to devastating land-loss and cultural marginalisation for M?ori at the hands of settlers and successive governments. This article examines the damaging effects of a Crown-imposed treaty claims settlement system designed to address injustices inflicted on M?ori. Interview data from a Taranaki-based (a West Coast region, central North Island of Aotearoa New Zealand) hap? (sub-tribe) that engaged with this system foreground the adversarial nature of this system and its continuation of trauma. We argue that, while the process provides voice to M?ori, it does so within a paradigm that pits kin-groups against each other, unjustly limits redress and fails to resolve tension. A tikanga framing provides insights into how tensions are set up and ways tikanga (underlying values and principles that guide practice) can be used outside the redress system to seek healing and resolution.
Keywords: colonial structures; colonisation; crown; hapū; kāwanatanga; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Cultural and intellectual property rights: a series of readers examining critical issues in contemporary Māori society - Pihama, Leonie; Smith, Cherryl Waerea-i-te-Rangi (Economics, politics & colonisation ; v. 2, 1997)
Keywords: civil Rights; colonisation; intellectual property; print only; treaty claims

The changing images of nineteenth century Māori society: from tribes to nation - Henare, Manuka Arnold (2003)
Keywords: colonisation; he whakaputanga; history; self-determination; thesis; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

The Conscientisation and Politicisation of Maori Women - Nepe, Tuki (Te Pua, 1992)
Keywords: colonisation; decolonisation; discrimination; economic inequality; inequality; intersectionality; mana wāhine; periodicals; sexism; wāhine māori

Tradition and change in Maori leadership - Walker, Ranginui (Research Unit for Maori Education, University of Auckland, 1993)
Keywords: capitalism; colonisation; government; government relations; imperialism; kīngitanga; land loss; land theft; leadership; mana whenua; māori battalion; rangatira; urbanisation

Chapter 18: The Treaty of Waitangi and Recognition of Tikanga Māori - Mikaere, Ani (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land tenure; law; race relations; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi

Hui Whakapiripiri: A Hui to discuss strategic directions for Māori Health Research: 3.1 Māori Health Research and Te Tiriti o Waitangi - Jackson, Moana (Te Ropu Rangahau Hauora a Eru Pomare, 1996)
Keywords: colonisation; kaupapa māori; māori rights; rangatiratanga; research policy; tiriti o waitangi/treaty of waitangi; turangawaewae

The face behind the law: The United Nations and the rights of indigenous peoples - Jackson, Moana (Yearbook of New Zealand jurisprudence, 2005)
In recent years Maori people have adopted many strategies to protect and advance the well being and visions implicit in the exercise of tino rangatiratanga. Much of that work has been done at home, but an increasing number of Iwi and other Maori organisations are now participating in international affairs that are seen to have some relevance to our lives. They are joining a worldwide movement by Indigenous Peoples to reassert their rights and reclaim their rightful place.
Keywords: UNDRIP; civil Rights; colonisation; crown law; imperialism; international law; international organization; racism; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Changing Realities : Unchanging Truths - Jackson, Moana (Conferrence on Folk Law and Legal Pluralism, 1994)
Keywords: assimilation; colonisation; crown; iwi; law; racism; rangatiratanga

Chapter 5: Where to next? Decolonisation and the stories in the land: Imagining Decolonisation - Jackson, Moana (Imagining Decolonisation, 2020)
Keywords: colonisation; decolonisation; hapū politics; iwi politics; rangatiritanga; tikanga | indigenous law

Colonization as myth-making - Jackson, Moana (Being indigenous: perspectives on activism, culture, language and identity, 2019)
Keywords: colonisation; crown; ethnic identity; government; land loss; land theft; political power; rangatiratanga; tiriti o waitangi/treaty of waitangi

Shaky Foundations: The fundamental flaw at the heart of a “model” treaty involving New Zealand and the Indigenous Māori community - Charters, Claire; Whare, Tracey (World Policy Journal, 2017)
In 1840, English officials on behalf of the British crown signed the Treaty of Waitangi—also known as Te Tiriti o Waitangi—with the Indigenous Māori population, affirming Māori sovereignty and guaranteeing their collective rights to the country’s land and resources. Since the 1700s, English settlers had been arriving in Aotearoa (the Māori name for New Zealand) to capitalize on the seal and whale trade. As the number of settlers increased, reports flowed back to Britain of general lawlessness and dubious private land deals, and the crown was forced to consider how best to control its citizens. A treaty with the Māori, officials decided, was the way to do so. The agreement, which established the basis for the relationship between the Māori and the British, is commonly cited as a shining example of how a treaty can recognize and protect Indigenous peoples’ rights by curtailing the reach of the state. But does te Tiriti live up to its sterling reputation? The answer, of course, is complicated.
Keywords: colonisation; crown policy; governance; kāwanatanga; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

Whakawhanaungatanga as a Māori Approach to Indigenous–Settler of Colour Relationship Building - Rata, Arama; Al-Asaad, Faisal (New Zealand Population Review, 2019)
Communities of colour are racialised and oppressed differentially by settler colonial states (Saranillio, 2013), yet the discourse of diversity and inclusion that dominates state interactions with communities of colour tends to conflate marginalised groups as equivalent and interchangeable to the detriment of intergroup relations. An approach to community building that recognises racial difference in general and the irreducibility of indigeneity in particular is needed if racialised communities are to create solidarities for transformative change. We engage Indigenous and settler colonial theories to address these imperatives, while noting the distinct character of these frameworks. In particular, we seek to highlight the specificity of indigeneity in settler colonial contexts, such as Aotearoa New Zealand, and to generate a model for relationship building that is not founded on settler colonial ideologies, by drawing on Indigenous concepts. Through thematic analysis of interviews with Māori community leaders, we explore Māori-–tauiwi (settler) of colour (ToC) relations. The results of our qualitative analysis provide evidence for Māori–ToC relations that are consistent with whanaungatanga (good relationships characterised as family-like, based on similar experiences, and bound in conditional solidarity; see Benton, Frame, and Meredith, 2013). Furthermore, we identify the following four aspects of whakawhanaungatanga (relationship building): positioning, power sharing, dialogue and cultural practice. Thus, we suggest whakawhanaungatanga as a Māori approach to relationship building with the potential to generate Indigenous–settler of colour solidarities towards transformative change.
Keywords: colonisation; diversity; relationship building; whanaungatanga

Te Pītau o te Tuakiri: Affirming Māori Identities and Promoting Wellbeing in State Secondary Schools - Rata, Arama (2012)
Numerous researchers have posited links between ethnic identity and psychological wellbeing (Phinney, 1992; Martinez & Dukes, 1997; Roberts, Phinney, Masse, Chen, Robers, & Romero, 1999; Houkamau & Sibley, 2011), and Māori cultural interventions have been suggested as a means of promoting a range of positive outcomes (e.g. M. Durie, 1998; Durie, 2003b; Lawson-Te Aho, 1998). However, longitudinal evidence of causal pathways between Māori ethnic identity and psychological wellbeing remains scarce, and evidence of the positive impacts of cultural interventions is not well documented. The present thesis investigates Māori identity development in the context of State secondary schools, and explores the relationships between Māori cultural engagement, Māori identity, and psychological wellbeing. A methodology that incorporates both mātauranga Māori (Māori knowledge) and Western scientific knowledge bases and research methods was applied. Interviews were held with Māori students and their whānau (families) at a State secondary school where a community-driven initiative to improve Māori student outcomes took place. Thematic analysis was used to generate Te Korowai Aroha Framework, outlining how Māori cultural initiatives can enable schools to fulfil their duty of care and meet Māori community needs by affirming individuals‟ cultural identity and agency, by building relationships based on mutual respect, and by working collaboratively within the school and with external services providers. Thematic analysis of these interviews was also conducted to generate The Pōwhiri Identity Negotiation Framework. The pōwhiri (formal welcome), in which Māori creation narratives are ritually re-enacted, is used as a metaphor for Māori identity negotiation. The stages of creation Te Kore, Te Pō, Te Whaiao, and Te Ao Marama are used to describe, respectively: those who were yet to display interest in Māori cultural identities; those who were interested in developing their Māori identities; those who were actively exploring their Māori identities; and those who felt secure in their Māori identities. Quantitative longitudinal survey data from over 300 Māori adolescents in the Youth Connectedness Project was then analysed. Structural Equation Modelling revealed that Māori cultural engagement positively predicted Māori ethnic identity, and that Māori ethnic identity positively predicted psychological wellbeing, in support of hypotheses. In addition, Hierarchical Linear Modelling revealed that the higher a school‟s level of Māori cultural promotion, the higher the ethnic identity of its students was likely to be. The results of this thesis demonstrate the impact of school cultural environments on individual identity development, and provide evidence that cultural engagement initiatives can enhance Māori identities, which in turn can increase psychological wellbeing. The results from the studies presented in this thesis are incorporated into Te Pītau o te Tuakiri framework, outlining how Māori identities can be nurtured, and the results are also used to offer guidelines for individuals wishing to become more engaged in Māori culture, and institutions wishing to become more responsive to Māori communities. These findings are used to challenge educators and policy makers to ensure schools and other State institutions support Māori cultural expression and affirm Māori identities.
Keywords: colonisation; education; identity; policy; wellbeing

The Colonising Environment: an Aetiology of the Trauma of Settler Colonisation and Land Alienation on Ngāi Tahu Whanau - Reid, John; Rout, Matthew; Tau, Maire; Smith, Cherryl (UC Ngāi Tahu Research Centre, 2017)
Keywords: colonisation; crown policy; intergenerational trauma; land loss; racism

Chapter 1: Reclaiming Māori education - Walker, Ranginui (Decolonisation in Aotearoa: Education, research and practice, 2016)
Keywords: assimilation; colonisation; education

Authenticating Mäori Physicality: Translations of ‘Games’ and ‘Pastimes’ by Early Travellers and Missionaries to New Zealand - Hokowhitu, Brendan (The International Journal of the History of Sport, 2008)
This paper theorizes how knowledge of indigenous tribal epistemologies was made ‘knowable’ through Enlightenment rationalism in an early colonial context. Specifically, the paper determines how and what knowledge of Mäori tribal physical activities was interpreted and authenticated through early travellers' tales and missionaries’ accounts in New Zealand. The central thesis argues that what was established as authentic and truthful aligned with Enlightenment rationalism, while those Mäori physical practices incomprehensible to Western understandings were deemed inauthentic and, consequently, were obscured and/or discarded. Throughout, the article theorizes the translation of knowledge into meaningful Western discourses and how these translations came to be crystallized in the colonial imagination.
Keywords: colonisation; cultural practices

Producing Elite Indigenous Masculinities - Hokowhitu, Brendan (Settler Colonial Studies, 2012)
Keywords: colonisation; gender; identity; masculinity; sovereignty; tiriti o waitangi/treaty of waitangi

Price of citizenship for Maori: A matter of historical and legal context - Warbrick, Paerau (Law & History, 2021)
This article explains that the concept of citizenship for Maori in New Zealand has evolved. The 'Native Rights Act 1865' declared all Maori to be subjects of the Crown. This implication then justified the confiscation of lands in the 1860s from those Maori deemed to be disloyal to the Crown. By the beginning of the twentieth century, politicians began to use the concept of citizenship to force Maori to fight in World War I. In the mid-twentieth century, the Maori politician Apirana Ngata used the term 'price of citizenship' to gain social and political rights for all Maori, as a result of the efforts of Maori soldiers fighting as New Zealand citizens in World War II.
Keywords: citizenship; civil Rights; colonisation; military

Behind the wire: Māori women and prison - McIntosh, Tracey (Women’s Studies Journal, 2017)
Keywords: colonisation; crown policy; incarceration; prison; wāhine māori

Prisoner Voting Rights and Wāhine Māori: An Exploration of the Relationship Between Wāhine Māori and the State - Morgan, Ella (ResearchSpace@Auckland, 2022)
In 2010, the Electoral (Disqualification of Sentenced Prisoners) Amendment Bill marked a significant change in prisoner voting rights policies in New Zealand, disenfranchising all prisoners regardless of sentence length. A decade later in 2020, the Electoral (Registration of Sentenced Prisoners) Amendment Bill re-enfranchised prisoners serving sentences of less than three years. Over this time, a Waitangi Tribunal Inquiry and a number of Māori politicians and public figures highlighted the disproportionate effects of prisoner disenfranchisement for Māori given over-representation of Māori in the prison population. However, less attention has focused on the specific effects of disenfranchisement for wāhine Māori (Māori women) in prison, and what this reflects about the relationship between wāhine Māori and the state. While women make up a significantly smaller percentage of the general prison population than men, wāhine Māori made up 61% of the women’s prison population in 2021 (Office of the Inspectorate, 2021). Additionally, wāhine Māori had a drastically different experience of colonisation to tāne Māori (Māori men). Colonial actions worked to destroy traditional Māori social organisation, which disrupted the balance between men and women and confined wāhine Māori to a social position that falls behind Pākehā men and women and Māori men. This thesis takes a Māori-centred, Mana Wahine lens to draw on the content of interviews with key informants and analysis of parliamentary readings of the 2010 and 2020 bills in order to explore how prisoner disenfranchisement in the 21st century reflects broader patterns regarding the treatment of wāhine Māori by the state. Disenfranchisement is likely to uniquely affect wāhine Māori due to their importance in te ao Māori as nurturers, the managers of households, and their centrality to the intergenerational transfer of knowledge. This not only presents barriers to voting and re-enrolment on the electoral roll post-release from prison, but also serves to practically disenfranchise the whānau and communities that wāhine Māori belong to. The lack of consideration of the needs and experiences of wāhine Māori in state discussions of prisoner voting rights mirrors the ongoing invisibility of wāhine Māori in state policy. The state has framed prisoner voting rights around male and tāne Māori norms, which cannot account for wāhine Māori. Moving forward, if prisoner voting rights policies are revisited in the future, an intersectional approach must be taken that effectively addresses the needs of wāhine Māori.
Keywords: colonisation; crown policy; crown violence; disenfranchisement; racism; voting rights; wāhine māori

The Humpty Dumpty Principle at work: The role of mistranslation in the British Settlement of Aotearoa. 'The Declaration of Independence' and 'He Whakaputanga o te Rangatiratanga o nga hapu o Nu Tireni' - Mutu, Margaret (For better or worse: translation as a tool for change in the South Pacific, 2014)
Keywords: colonisation; he whakaputanga; oceania

Chapter Four: The Treaty of Waitangi in the Postcolonial Era - Walker, Ranginui (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land march; land tenure; post-colonialism; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

The State of Māori rights - Mutu, Margaret (Huia, 2015)
The State of Maori Rights brings together a set of articles written between 1994 and 2009. It places on record the Maori view of events and issues that took place over these years, issues that have been more typically reported to the general public from a 'mainstream' media perspective. It is an important documentation of these fifteen years of New Zealand history, recording the assertion of Maori rights as the indigenous people of Aotearoa New Zealand, focusing on Maori issues and experiences and written from a Maori perspective.
Keywords: civil Rights; colonisation; crown violence; foreshore and seabed act 2004; government relations; intergenerational trauma; kāwanatanga; mana motuhake; māori electorates; māori rights; race relations; racism; te pāti māori; tiriti o waitangi/treaty of waitangi; voting; waitangi tribunal

Ngāti Kahu: portrait of a sovereign nation: history, traditions and Tiriti o Waitangi claims / Kia pūmau tonu te mana motuhake o ngā hapū o Ngāti Kahu - Mutu, Margaret; Pōpata, Lloyd; Williams, Te Kani; Herbert-Graves, Ānahera; Rēnata, Reremoana; Cooze, JudyAnn; Pineaha, Zarrah; Thomas, Tania; Kingi-Waiaua, Te Ikanui; Te Rūnanga-a-Iwi o Ngāti Kahu; Wackrow Williams and Davies Ltd (Huia Publishers, 2017)
"This book describes the iwi of Ngāti Kahu through the traditions and histories of each of the sixteen hapū, told by kuia and kaumātua and kept alive for future generations. These include histories of poverty, deprivation and marginalisation at the hands of the Crown, and loss of lands of the iwi. The book examines the range of techniques used by the Crown to justify its actions and the way these laid the groundwork for continuing injustices. The remedies needed to redress these injustices and achieve reconciliation of Ngāti Kahu and the Crown are set out. These include constitutional change to achieve the restoration of political, social and economic well-being to Ngāti Kahu, Crown relinquishment of all Ngāti Kahu lands to their rightful owners and payment of sufficient compensation to ensure no further Treaty of Waitangi claims. This history of Ngāti Kahu details the range of Crown actions against Ngāti Kahu to the current day, the effects of these actions on the people of Ngāti Kahu and the concerted and continuing efforts by Ngāti Kahu for remedies and reconciliation with the Crown"--Publisher information.
Keywords: colonisation; constitutional transformation; government relations; hapū; history; kāwanatanga; kōrero nehe; mana motuhake; ngāti kahu; noho-ā-iwi; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; treaty claims; tūpuna

Behind the smoke and mirrors of the Treaty of Waitangi claims settlement process in New Zealand: no prospect for justice and reconciliation for Māori without constitutional transformation - Mutu, Margaret (Journal of Global Ethics, 2018)
Governments in New Zealand have legislated a large number of settlements extinguishing many hundreds of claims taken by Māori against the Crown for breaches of the country’s founding document, Te Tiriti o Waitangi. They portray settlements as a great success for Māori and the Crown. Māori disagree. Settlements are government-determined and imposed on Māori using a smoke and mirrors approach that masks successive governments’ true intentions: to claw back Māori legal rights; to extinguish all claims; and to maintain White control over Māori. In short, to uphold the Doctrine of Discovery in further breach of Te Tiriti o Waitangi. Māori claimants and negotiators report being enticed into the process by false promises only to become traumatised and disenchanted. Yet many take a pragmatic stance and sign settlements, making the best they can out of a bad deal that goes nowhere near compensating for their actual loss. They know that despite what legislation may say, the settlements are not full, not fair and not final and that, like all previous settlements, they will be revisited. They also know that unless fundamental changes are made to the constitutional makeup of the country, there is no prospect of justice and reconciliation for Māori.
Keywords: colonisation; constitutional transformation; doctrine of discovery; kāwanatanga; tiriti o waitangi/treaty of waitangi; trauma; treaty settlements; waitangi tribunal

The treaty claims settlement process in New Zealand and its impact on Māori - Mutu, Margaret (2019)
This article considers research conducted on the impact of the Crown’s treaty claims settlement policy on Māori in New Zealand. It provides a brief background to the Treaty of Waitangi and the subsequent British colonisation process that relied on the Doctrine of Discovery in breach of the treaty. It outlines how colonisation dispossessed Māori of 95 percent of their lands and resources, usurped Māori power and authority and left them in a state of poverty, deprivation and marginalisation while procuring considerable wealth, prosperity and privilege for British settlers. The work of the Waitangi Tribunal, the commission of inquiry set up to investigate those breaches, is considered, as is the Crown’s reaction to the 1987 Lands case in developing its treaty claims settlement policy. The Crown unilaterally imposed the policy despite vehement opposition from Māori. Since 1992, it has legislated more than seventy ‘settlements’. The research shows that overall, the process has traumatised claimants, divided their communities, and returned on average less than one percent of their stolen lands. Proposals for constitutional transformation have drawn widespread support from Māori as a solution to British colonisation. United Nations treaty-monitoring bodies have recommended that the government discuss this with Māori
Keywords: colonisation; constitutional transformation; crown policy; law; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Mana Maori motuhake Maori concepts and practices of sovereignty - Mutu, Margaret (Routledge handbook of critical indigenous studies, 2021)
Keywords: colonisation; ethnicity; he whakaputanga; mana motuhake; rangatiratanga

‘To honour the treaty, we must first settle colonisation’ (Moana Jackson 2015): the long road from colonial devastation to balance, peace and harmony - Mutu, Margaret (Journal of the Royal Society of New Zealand, 2019)
Māori leaders in New Zealand continue the battle to end British colonisation. The aim is to restore the balance between Māori and the Crown guaranteed in the treaty that Māori and the British Crown agreed to in 1840 so that we can live in peace and harmony. Early European visitors subjected our ancestors to numerous atrocities. Relying on the Doctrine of Discovery, they illegitimately usurped our power and dispossessed us, leaving us in a state of poverty, deprivation and marginalisation. They fabricated myths to justify their criminal activities, set up an illegitimate parliament with unfettered powers, passed laws legalising their crimes and then covered it up with amnesia. They established the Waitangi Tribunal in 1975 to inquire into breaches of the treaty, not realising that it would dismantle the myths and look beneath the amnesia. Governments then instigated the ‘treaty claims settlement’ process to extinguish all Māori claims, remove Māori rights and entrench colonisation. Research undertaken has shown that Māori loathe this process and do not accept that settlements are full and final. Research on constitutional transformation has identified a possible solution. The first step towards that goal involves implementing the United Nations Declaration on the Rights of Indigenous Peoples.
Keywords: UNDRIP; colonisation; colonisation myths; constitutional transformation; crown; kāwanatanga; māori rights; oral history; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; treaty breaches; treaty settlements; waitangi tribunal

Ko te whenua te utu = Land is the price essays on Maori history, land and politics. - Sorrenson, M. P. K. (Auckland University Press, 2014)
For more than half a century, Keith Sorrenson - one of New Zealand's leading historians and himself of mixed Maori and Pakeha descent - has dived deeper than anyone into the story of two peoples in New Zealand. In this new book, Sorrenson brings together his major writing from the last 56 years into a powerful whole, covering topics from the origins of Maori (and Pakeha ideas about those origins), through land purchases and the King Movement of the nineteenth century, and on to twentieth-century politics and the new history of the Waitangi Tribunal.
Keywords: colonisation; history; kīngitanga; kōrero nehe; land tenure; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Tino rangatiratanga : water under the bridge? - Bargh, Maria (He pūkenga kōrero: a journal of Māori studies, 2007)
Argues that Māori have been actively engaged in practising tino rangatiratanga in various forms even since before the Declaration of Independence ...
Keywords: colonisation; constitution; government; international relations; iwi; kaitiakitanga; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; water rights

Unearthing (de)colonial legal relations: Mining law in Aotearoa New Zealand - Bargh, Maria; Wagner, Estair Van (Decolonizing law: Indigenous, third world and settler perspectives, 2021)
Keywords: colonisation; crown policy; decolonisation; environment; tiriti o waitangi/treaty of waitangi

Chapter 40: Indigenous finance: treaty settlement finance in Aotearoa New Zealand - Bargh, Maria (The handbook of diverse economies, 2020)
"Theorising and illustrating diverse, more-than-capitalist economies, this broad-ranging Handbook presents ways in which it is possible to imagine and enact other ways of being. It gathers together empirical examples of diverse economic practices and experiments from across the world, framed by in-depth discussions of key theoretical concepts. Organised into thematic sections, the Handbook moves from looking at diverse forms of enterprise, to labour, transactions, property, and finance as well as decentred subjectivity and diverse economies methodology. Chapters present a wide diversity of economic practices that make up contemporary economies, many of which are ignored or devalued by mainstream economic theory. Pushing the boundaries of economic thinking to include more than human labour and human/non-human interdependence, it highlights the challenges of enacting ethical economies in the face of dominant ways of thinking and being. Economic geography, political economy and development studies scholars will greatly appreciate the empirical examples of diverse economic practices blended with theory throughout the Handbook. It will also benefit policy-makers and practitioners working within diverse economies, or looking to create more ethical ways of living"-- Provided by publisher.
Keywords: colonisation; economic aspects; governance; land loss; land ownership; tiriti o waitangi/treaty of waitangi; treaty settlements

How should we teach about Te Tiriti o Waitangi? Issues for raraunga (citizenship) education - Bargh, Maria; Macfarlane, Angus (Our Civic Future, 2018)
Keywords: colonisation; policy; tiriti o waitangi/treaty of waitangi

He Pōkēkē Uenuku I Tū Ai: A Quantitative Exploration of Māori Identity, Political Attitudes, and Behaviour - Greaves, Lara (ResearchSpace@Auckland, 2017)
To be Māori is to be political. Our history is filled with political struggles and victories. These struggles, originating from experiences of colonisation and assimilation, have greatly influenced what it is to be Māori today. This thesis explores the relationship between Māori ethnic identity, and political attitudes and outcomes. In this thesis, I present five studies (across four published papers and one full manuscript) which validate the Multidimensional Model of Māori Identity and Cultural Engagement (MMM-ICE2). I focus particular attention on the scale’s Socio- Political Consciousness dimension, and illustrate the links between identity and politics for Māori. The MMM-ICE2 is a seven-dimension scaled designed with Māori, by Māori, and for Māori to measure Māori ethnic identity (Houkamau & Sibley, 2010, 2015a). In the first two studies, I focus on using psychometric techniques to further validate the MMM-ICE2 as a measurement tool. Firstly, I use random intercept exploratory factor analysis to show that the scale is not vulnerable to acquiescent responding (yea-saying; Greaves, Houkamau, & Sibley, 2017). The second study uses multigroup confirmatory factor analysis to illustrate that the MMM-ICE2 shows reasonable measurement equivalence across diverse Māori groups (Greaves, Manuela et al., 2017). In the third study of the thesis, I demonstrate that Māori, broadly defined, are more likely to vote for the political left – the Labour, Green, and New Zealand First parties – over the centre-right National Party (Greaves, Robertson et al., 2017). The results lay the groundwork for two further studies, which demonstrate the construct validity of the Socio-Political Consciousness dimension of the scale by predicting a range of political attitudes and behaviours. Study Four shows that, above and beyond the effects of demographics, Māori enrolled to vote on the Māori electoral roll were higher on the Socio-Political Consciousness and Group Membership Evaluation dimensions (Greaves, Osborne, Houkamau, & Sibley, 2017). Additionally, in Study Five, I demonstrate that higher Socio-Political Consciousness for Māori is related to higher levels of support for Māori rights protests, the left-wing Green Party, and the Māori-issue focussed, Māori and Mana political parties (Greaves, Sengupta et al., 2017). Yet, lower levels of Socio-Political Consciousness were related to higher support for the right-wing National Party. Taken together, these studies show that the MMM-ICE2 scale and the Socio-Political Consciousness dimension can predict important, realworld political outcomes and attitudes for Māori. Finally, I discuss the contributions that the papers in this thesis have made to the literature, and the inevitable limitations of the research. I then provide future research directions for the study of quantitative Māori identity and for Māori political participation more generally. I finish with reflections on the process of writing this thesis and on being an emerging Māori quantitative researcher.
Keywords: colonisation; identity; kāwanatanga; māori electorates; political participation

Reconciliation as Public Theology: Christian Thought in Comparative Indigenous Politics - O’Sullivan, Dominic (International Journal of Public Theology, 2014)
Abstract Christian public theology extends reconciliation beyond its principal sacramental concern for relationships between God and penitent to the construction of ‘socially just’ public relationships for the settlement of intra-national conflict. In theological terms, reconciliation brings public relationships into what Hally calls ‘the Christ narrative of passion, death and resurrection’ in which the perpetrators of injustice repent and seek forgiveness. This article introduces the conflicts that these discourses aim to resolve in Australia, Fiji and New Zealand and explains and contrasts reconciliation’s relative importance in each of these jurisdictions. Moreover, the article’s cross-jurisdictional comparison shows reconciliation’s limits and possibilities as public theology, and argues that in Australia and New Zealand it has helped to create political environments willing to admit indigenous perspectives on a range of policy issues. On the contrary, however, the article also shows that the Fijian churches have distorted the concept of reconciliation to support political imperatives that are difficult to rationalize theologically, even though they are presented by the churches as being concerned with religious goals.
Keywords: christianity; colonisation; kāwanatanga; reconciliation; religion

Anti-Colonial Abolitionism: International Context - Pranteau, Sheri; McIntosh, Tracey; Anthony, Thalia; Chartrand, Vicki (Journal of Prisoners on Prisons, 2022)
Keywords: colonisation; crown policy; prison abolition; racism; systematic racism

A Māori perspective of being and belonging - Rameka, Lesley (Contemporary Issues in Early Childhood, 2018)
Belonging and being are inextricably linked. From a M?ori perspective, belonging and being can be viewed through a number of interconnected historical and contemporary frames. One frame is derived from M?ori perceptions of the creation of the universe and genealogical relationships to the universe and everything in it. Another frame of belonging and being stresses increasingly diverse and complex positionings that require negotiation of radically different terrains of assumptions, behaviours, values and beliefs. This article explores two interrelated aspects of being and belonging from a M?ori perspective: whakapapa (?genealogical connections?) and whanaungatanga (?family relationships?). It discusses how each aspect has changed over time as a result of colonisation, urbanisation and western education, and identifies how the reflection of each has been transformed.
Keywords: belonging; colonisation; education; urbanisation; whakapapa; whanaungatanga

Unfolding tensions within post-settlement governance and tribal economies in Aotearoa New Zealand - Mika, Jason Paul; Smith, Graham Hingangaroa; Gillies, Annemarie; Wiremu, Fiona (Journal of Enterprising Communities: People and Places in the Global Economy, 2019)
Purpose This paper aims to examine indigenous governance and economies of iwi Maori (Maori tribes) in Aotearoa New Zealand. Research into persisting inequities amongst iwi that have settled treaty claims and the potential for intervention through new governance models and indigenous entrepreneurship contextualise the paper. Design/methodology/approach Kaupapa Maori (Maori philosophy) is used as an indigenous methodology to facilitate and empower transformative change, underpinned by Maori knowledge, language and culture. A multi-level approach is used to collect data from international, national and local tribal organisations. Validity is established through stakeholder engagement. Findings A central challenge in the post-treaty settlement context is exponentialising tribal capabilities because of the multiple purposes ascribed to post-settled iwi. Four themes, characterised as “unfolding tensions”, offer a critique and basis for solving tribal development challenges: how do tribes create culturally grounded global citizens; how do tribes rebalance wealth creation and wealth distribution; how do tribes recalibrate tribal institutions; and how do tribes embed entrepreneurship and innovation within their economies? Research limitations/implications As data collection is still underway, the paper is conceptual. Practical implications Five strategies to address unfolding tensions are identified for tribes to consider. Social implications Tribal governors and tribal members are implicated in the analysis, as well as the architects of post-treaty settlement governance models. Originality/value The paper contributes to theorising about tribal governance, economies and entrepreneurship.
Keywords: colonisation; indigenous economics; indigenous entrepreneurship; indigenous governance; mana motuhake; māori economies; post-settlement (waitangi tribunal); tribal development

Indigenous environmental defenders in Aotearoa New Zealand: Ihumātao and Ōroua River - Mika, Jason Paul; Dell, Kiri; Elers, Christine; Dutta, Mohan; Tong, Qing (AlterNative: An International Journal of Indigenous Peoples, 2022)
This article theorises the question?what is the role and nature of Indigenous environmental defenders in Aotearoa New Zealand? We explore M?ori?the Indigenous people of Aotearoa New Zealand?who act as environmental defenders of their lands and waters despite the perpetual insecurity of their constitutional rights and imbalances in power and resources compared with state and corporate actors. The environmental defence of Aotearoa New Zealand by M?ori began with the arrival of European explorers? intent on overturning Indigenous institutions of environmental management that has sustained their peoples for a thousand years. Stemming from case study analysis of M?ori environmental defenders at Ihum?tao in M?ngere and ?roua River in Manawat?, we propose whenua (land) resilience theory to explain the concomitance of environmental defence and development from an Indigenous perspective.
Keywords: colonisation; environment; kaitiakitanga; land protection

The Role of Emotion in Understanding Whiteness - Borell, Belinda (Journal of Bioethical Inquiry, 2021)
This paper argues that stoicism as a central element of whiteness shapes, controls, and ultimately limits the experience and expression of emotion in public space. I explore how this may play out in particular medical settings like hospitals in Aotearoa New Zealand. I argue that working in conjunction with other values of whiteness identified by Myser (2003)—hyper-individualism, a contractual view of relationships, and an emphasis on personal control and autonomy—this makes hospitals emotionally unsafe spaces for Māori and other groups who place high importance in the collective sharing of emotion. Using death and bereavement as an example, I suggest that challenging and addressing stoicism in the structure and performance of whiteness in hospital settings may provide an important point of entry for anti-racism measures and health equity.
Keywords: colonisation; health; healthcare; identity; racism; white privilege

Conceptualising historical privilege: the flip side of historical trauma, a brief examination - Borell, Belinda; Moewaka Barnes, Helen; McCreanor, Tim (AlterNative: An International Journal of Indigenous Peoples, 2018)
Historical trauma is an important and growing area of research that provides crucial insights into the antecedents of current-day inequities in health and social wellbeing experienced by Indigenous people in colonial settler societies. What is not so readily examined is the flip side of historical trauma experienced by settlers and their descendants, what might be termed ?historical privilege?. These historic acts of privilege for settlers, particularly those emigrating from Britain, provide the antecedents for the current-day realities for their descendants and the structural, institutional and interpersonal levels of advantage that are also a key feature of inequities between Indigenous and settler. This article theorises an explicit link between historical trauma and historical privilege and explores how the latter may be examined with particular reference to Aotearoa New Zealand. Three core elements of historical trauma are posited as a useful framework to apply to historical privilege.
Keywords: colonisation; trauma

'Pissed Off and Confused'/'Grateful and (Re)Moved': Affect, Privilege and National Commemoration in Aotearoa New Zealand - McConville, Alex; Wetherell, Margaret; McCreanor, Tim; Borell, Belinda; Moewaka Barnes, Helen (Political Psychology, 2020)
This article explores affect, colonial privilege, and the cultural politics of national commemoration in Aotearoa New Zealand. Based on focus‐group interviews around two major national days, we examine means through which feelings and emotions are deployed in ways that enable the reproduction of social advantage. Situating affect within patterns of relationship, four interrelated affective‐discursive practices are explored. In relation to Waitangi Day, agents tend to work under the rubric of anger and confusion. For Anzac Day, being grateful and moved shapes the interaction, although participants often indicate preferences towards "having a day off." Given the colonial context in which these practices circulate, analysis observes the associated freedom and ease by which affective‐discursive privilege is (re)produced. Often incongruent and rarely challenged, privilege allows associated actors to do what they want, when they want, however they want. This affective climate authorizes the ongoing reproduction of, and justification for, membership to a higher‐status ethnic group of which unearned opportunities and entitlements remain its everyday, expected currency.
Keywords: colonisation; memorialisation; national identity; white privilege

Ka Pu Te Ruha, Ka Hao Te Rangatahi - Kukutai, Tahu; Webber, Melinda (1995)
Keywords: colonisation; demographic aspects; identity

Tracing Opuatia: Repatriating and repurposing colonial land data - Kukutai, Tahu; Whitehead, Jesse; Kani, Heeni (New Zealand Geographer, 2022)
Māori land data produced through colonial systems of dispossession lack interoperability, preventing kin-based communities from tracking their land. Our novel approach to repatriate and harmonise historic land data traces the history of the 45,500 acre Opuatia Block allocated to hapū Ngāti Tiipa in 1866, following the confiscation of 1.2 million acres of Waikato land. Ngāti Tiipa resisted Crown and settler pressures for 30 years, but 80% of Opuatia was alienated within a decade. We discuss the devastation of ‘judicial raupatu’ and the implications of this work for hapū data sovereignty and wider international efforts to achieve Indigenous data sovereignty.
Keywords: colonisation; data sovereignty; hapū; indigenous data sovereignty; iwi; māori land data; repatriation

Rangatiratanga: Narratives of Racism, Resistance, and Well-being - Smith, Dr Cherryl; Tinirau, Rāwiri; Rattray-Te Mana, Helena; Moewaka Barnes, Helen; Cormack, Donna; Fitzgerald, Eljon (Whanganui: Te Atawhai o Te Ao., 2021)
Keywords: colonisation; racism; rangatiratanga; self-determination; wellbeing

Understanding Maori 'lived' culture to determine cultural connectedness and wellbeing - Reid, John; Varona, Golda; Fisher, Martin; Smith, Cherryl (Journal of Population Research, 2016)
Maori tribal authorities have sought to measure the wellbeing of their people as a baseline for determining the extent to which their economic, social, and cultural goals are being achieved. In recent years, data from government-administered social surveys and/or censuses have become a significant source of information. Using the tribal authority of Te Runanga o Ngai Tahu (TRONT) as a case study, this paper explores and compares data concerning Ngai Tahu wellbeing contained in two recently completed TRONT reports: the Ngai Tahu State of the Nation 2015 report (a quantitative study derived from government-administered survey data); and, the preliminary findings from the Ngai Tahu Whenua Project (a qualitative study undertaken by TRONT). Both studies present similar results regarding levels of tribal economic wellbeing, however, they show different results in regards to levels of cultural wellbeing. The qualitative study reveals reasonably high levels of cultural engagement among participants. Conversely, the quantitative study demonstrates reasonably low levels of cultural engagement. The difference is explained in each study's approach to understanding culture. The quantitative study viewed culture as engagement in 'static' cultural practices, whereas the qualitative study viewed Maori culture as a 'lived' set of deep networks and connections between individuals, their whanau (extended family), and places of symbolic cultural importance (particularly land and water). It is argued that measuring 'lived' culture would provide a better means of ascertaining cultural wellbeing. It is suggested that a useful means of measuring Maori lived culture would be to determine the quality and depth of relational networks.
Keywords: colonisation; ethnicity; health; iwi; wellbeing

Towards a Social-Structural Model for Understanding Current Disparities in Maori Health and Well-Being - Reid, John; Taylor-Moore, Karyn; Varona, Golda (Journal of Loss and Trauma, 2014)
Colonization has resulted in Maori occupying a vulnerable position in New Zealand society. Comparatively poor health, along with complex social and economic problems, is a reflection of this fundamental insecurity. This article aims to put forward a historical and developmental perspective for understanding some of the current health disparities experienced by Maori, by exploring the concepts of historical trauma, loss of land, and alternative theories of development from post-development theory.
Keywords: colonisation; health; historical trauma; land loss

Indigenous Peoples, Data, and the Coloniality of Surveillance - Cormack, Donna; Kukutai, Tahu (New Perspectives in Critical Data Studies: The Ambivalences of Data Power, 2022)
In Aotearoa New Zealand (Aotearoa NZ), Māori (the Indigenous peoples of New Zealand) have long been objects of surveillance by state institutions and agents. State representations have centred on constructions of difference and deviance, on understandings of Indigenous peoples as dangerous, and on the management of Indigenous resistance to colonialism. This chapter considers how contemporary state surveillance practices in Aotearoa NZ, enabled by the expanded use of big data and linked government datasets, function to regulate and manage Māori. Through this lens, we explore continuities of current data practices for Indigenous peoples with the racialised logics and social orders set in place as part of global systems of imperialism and colonialism. Recognising that resistance has always been a part of Indigenous responses to colonialism, we also explore how Māori Data Sovereignty (MDSov), as part of broader Indigenous Data Sovereignty (IDS) movements globally, provides opportunities to counter and disrupt prevailing data relations and to imagine alternative futures.
Keywords: colonisation; data; data sovereignty; indigenous data sovereignty; surveillance

Beyond the “Abyssal Line”: Knowledge, Power, and Justice in a Datafied World - Cormack, Donna; King, Paula (The Oxford Handbook of Indigenous Sociology, 2021)
Colonization fundamentally disrupted Indigenous knowledge systems, establishing epistemic hierarchies that privilege Eurocentric colonial epistemologies and methodologies. In this chapter, the authors explore how epistemic hierarchies are (re)produced in the current context of “big data” and datafication, in particular for mokopuna Māori in the nation-state known as New Zealand (NZ). (We use the concept of “mokopuna Māori” to refer to and position Māori babies, children, and young people within the Māori world as the sacred reflection of our ancestors and a blueprint for future generations.) The chapter then considers the possibilities for Indigenous epistemic justice in the “zone of nonbeing” or beyond the “abyssal line.”
Keywords: colonial methodology; colonisation; data; data sovereignty; heirarchy; kaupapa māori; methodology

Returning the indigenous to the centre: a view from Aotearoa/New Zealand - DeSouza, Ruth; Cormack, Donna (Diversity in Health and Social Care, 2009)
Keywords: colonisation; discrimination; identity; māori rights; social aspects; social justice

Mana motuhake ā-raraunga: datafication and social science research in Aotearoa - Kukutai, Tahu; Cormack, Donna (Kōtuitui: New Zealand Journal of Social Sciences Online, 2019)
Keywords: census; colonisation; data; ethics; statistics

Indigenous Peoples' Data During COVID-19: From External to Internal - Carroll, Stephanie Russo; Akee, Randall; Chung, Pyrou; Cormack, Donna; Kukutai, Tahu; Lovett, Raymond; Suina, Michele; Rowe, Robyn K. (Frontiers in Sociology, 2021)
Global disease trackers quantifying the size, spread, and distribution of COVID-19 illustrate the power of data during the pandemic. Data are required for decision-making, planning, mitigation, surveillance, and monitoring the equity of responses. There are dual concerns about the availability and suppression of COVID-19 data; due to historic and ongoing racism and exclusion, publicly available data can be both beneficial and harmful. Systemic policies related to genocide and racism, and historic and ongoing marginalization, have led to limitations in quality, quantity, access, and use of Indigenous Peoples' COVID-19 data. Governments, non-profits, researchers, and other institutions must collaborate with Indigenous Peoples on their own terms to improve access to and use of data for effective public health responses to COVID-19.
Keywords: colonisation; covid-19; data; data sovereignty; inequity; racism; self-determination

The field of Indigenous health and the role of colonisation and history - Axelsson, Per; Kukutai, Tahu; Kippen, Rebecca (Journal of Population Research, 2016)
Keywords: Inequity; colonisation; disparities; displacement; health; health outcomes

Recognition and indigenizing official statistics: Reflections from Aotearoa New Zealand and Australia - Kukutai, Tahu; Walter, Maggie (Statistical Journal of the IAOS, 2015)
In First World colonised nations such as Aotearoa New Zealand and Australia, population statistics form the evidentiary base for how Indigenous peoples are known and `managed' through state policy approaches. Yet, population statistics are not a neut
Keywords: colonisation; crown policy; data sovereignty; identity; policy; self-determination; statistics

Chapter 2: "Publishing the Space": Data sovereignty and self-determination in Aotearoa New Zealand - Kukutai, Tahu; Cormack, Donna (Indigenous Data Sovereignty and Policy, 2020)
This book examines how Indigenous Peoples around the world are demanding greater data sovereignty, and challenging the ways in which governments have historically used Indigenous data to develop policies and programs. In the digital age, governments are increasingly dependent on data and data analytics to inform their policies and decision-making. However, Indigenous Peoples have often been the unwilling targets of policy interventions and have had little say over the collection, use and application of data about them, their lands and cultures. At the heart of Indigenous Peoples’ demands for change are the enduring aspirations of self-determination over their institutions, resources, knowledge and information systems. With contributors from Australia, Aotearoa New Zealand, North and South America and Europe, this book offers a rich account of the potential for Indigenous data sovereignty to support human flourishing and to protect against the ever-growing threats of data-related risks and harms.
Keywords: colonisation; data sovereignty; policy; self-determination

‘Colonised by a rich pākehā’: the metaphorical characterisation of the Internet Mana alliance - Peters, Rachel; Hocking, Darryl (Media International Australia, 2022)
In 2014, the Internet Mana alliance unsuccessfully ran in the New Zealand general election gaining just 1.42% of the party vote and failing to secure an electorate seat. The leaders of the alliance attributed their poor election result to the narratives constructed by the mainstream media, which they believed negatively influenced the public?s perception of Internet Mana. This study agrees that the mainstream media was complicit in the alliance?s poor election result, and drawing upon the discourse dynamics framework for metaphor analysis, it shows how these potentially damaging public narratives were predominantly constituted through complex sets of systematic metaphors which together created broader schematic frames or conceptual scenarios and carried certain evaluative and attitudinal perceptions. This analysis shows how systematic metaphors such as the internet mana alliance is a marriage of convenience and the internet mana alliance is a colonial trade were used to construct a negative public narrative.
Keywords: colonisation; elections; mainstream media; political parties

Decolonizing politics with insights from Indigenous Studies - Bargh, Maria (Identities, 2022)
Keywords: colonisation; decolonisation; education; mātauranga māori; rangatiratanga; tikanga | indigenous law

Colonisation, hauora and whenua in Aotearoa - Moewaka Barnes, Helen; McCreanor, Tim (Journal of the Royal Society of New Zealand, 2019)
Colonisation has deeply harmed Maori communities, seriously and consistently undermining their vitality, aspirations and potentials, particularly since the 1860s, at inestimable cost to the entire nation. The British arrival in Aotearoa commenced a relationship between two very different peoples that has profoundly influenced their distinct and collective fortunes ever since. Despite manifest breaches of te Tiriti o Waitangi, this relationship has centred settler interests ensuring that Maori sovereignty has been displaced in favour of colonial hegemony, entrenching longstanding, preventable inequities in health and other important domains of social life. In this paper we trace some broad indicators of relational health and wellbeing in Aotearoa and consider how Maori thinking about whenua, health and wellbeing might lead healing opportunities for people and whenua. We outline ways in which a unified, dynamic, relational Maori concept based on whenua as the determinant of health could contribute. We believe this could expand, strengthen and revitalise prevention, protection and promotion approaches, to counter the injustices of colonisation, contribute toward health equity and move toward just, sustainable shared futures for the benefit of all New Zealanders.
Keywords: colonisation; disparities; hauora; health; policy; regeneration; social determinants; sovereignty; tiriti o waitangi/treaty of waitangi; whenua